Academic Performance of Students in Primary Schools: A Study in Paschim Medinipur District of West Bengal (International Journal of Innovative Research in Engineering & Management, 2023)
Education is vital component of human  capital formation. Its development put forward the socio economic developments of the country also enhance the political awareness among the society. Therefore, quality  education is very much necessary for the development of  the entire country. This paper examines the students’  quality in primary education in Paschim Medinipur district  of West Bengal. The study is based on primary survey on  305 students from 7 schools scattered over different  regions in the district. The study tries to identify the  influencing factors of students’ academic performance. The results find moderate performance of students in  reading ability and simple numeracy. Parental occupation  and mother’s education are found significant influencing  determinants of students’ academic performance.
Keywords: Primary Education; Academic Performance; Parental Occupation; Mother’s Education; Private Tuition